2020
DOI: 10.1002/lary.28852
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Dysmotility is Common in Patients With Multiple System Atrophy

Abstract: Objectives: Esophageal dysmotility (ED) in patients with multiple system atrophy (MSA) are poorly understood. This study aimed to investigate the prevalence of ED in patients with MSA and to assess the relationship of esophageal abnormalities with other clinical findings and characteristics in these patients. Methods: A retrospective chart review was conducted to identify patients with MSA and to compare them to the elderly controls without MSA (65+ years) who underwent a videofluorographic esophagram from 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…We identified DES as an oesophageal dysfunction in a patient with MSA, using high-resolution oesophageal manometry. Previous studies of MSA demonstrated oesophageal dysfunction, including incomplete relaxation of the UES during swallowing 3 , abnormal UES resting pressure, abnormal deglutitive proximal oesophageal contraction [ 7 , 8 ], and oesophageal hypomotility [ 2 ]. Although most studies have focused on upper oesophageal dysfunction, we identified DES by evaluating the entire oesophagus.…”
Section: Discussionmentioning
confidence: 99%
“…We identified DES as an oesophageal dysfunction in a patient with MSA, using high-resolution oesophageal manometry. Previous studies of MSA demonstrated oesophageal dysfunction, including incomplete relaxation of the UES during swallowing 3 , abnormal UES resting pressure, abnormal deglutitive proximal oesophageal contraction [ 7 , 8 ], and oesophageal hypomotility [ 2 ]. Although most studies have focused on upper oesophageal dysfunction, we identified DES by evaluating the entire oesophagus.…”
Section: Discussionmentioning
confidence: 99%
“…The comparative value was calculated by dividing the diameter of the esophagus after esophageal contraction by the maximally dilated esophageal diameter, and an ED grade of 0 was defined as a value of 20% or less, grade 1 as 20-50% value, grade 2 as 50-80% value, and grade 3 as value of 80% or more (Figure 1A). The esophagus, as visualized fluoroscopically, was anatomically divided into three sections based on a revised classification of previous reports [19,20]: (1) cervical esophagus: proximal to the clavicles, (2) upper thoracic esophagus: from the clavicles distal to the tracheal bifurcation, and (3) mid-lower thoracic esophagus: from the tracheal bifurcation to the lower esophageal sphincter. ED grade was evaluated at these locations, and the ED score was defined as the sum of the ED grades at the three sites (Figure 1B).…”
Section: Methodsmentioning
confidence: 99%
“…ED grade was evaluated at these locations, and the ED score was defined as the sum of the ED grades at the three sites (Figure 1B). Herein, an ED score ≥ 3 was defined as having apparent esophageal dysmotility, since even healthy elderly patients without esophageal symptoms have mild esophageal dysmotility (ED score 1-2) [20]. The PAS and ED scores were evaluated based on a consensus between two otolaryngologists with at least 10 years of experience.…”
Section: Methodsmentioning
confidence: 99%
“…Esophageal peristalsis is originally evaluated by decreasing the velocity of the contrast medium through the esophagus and re ecting the residue of the contrast medium in the esophagus 22 . In order to evaluate lower esophageal peristalsis in SSc, we divided the lower esophagus into three parts (lower thoracic esophagus, middle thoracic esophagus, and upper thoracic esophagus or higher) based on previous studies 23 . In the esophageal phase, scales were de ned as follows; "0: none" grade represents no residue; "1: mild" means less than half of lower esophageal sphincter (LES) to tracheal bifurcation; "2: moderate" means more than half of LES to tracheal bifurcation; "3: severe" means above the tracheal bifurcation.…”
Section: Video Uoroscopic (Vf) Swallowing Studymentioning
confidence: 99%